Pericecal hernia: An unusual cause of abdominal pain in a child - Mugdha Anand; Puneet Kaur Sahi (Wolters Kluwer Medknow Publications, 2021)
Background: Internal hernias involve prolapse of any viscus through normal or abnormal mesenteric or peritoneal aperture and constitute <1% of all cases of hernia. Pericecal hernia is one form of internal hernia rarely reported in the pediatric population. Clinical Description: We describe the case of a 10-year-old boy with underlying tetralogy of Fallot, who presented with third episode of severe abdominal pain, requiring hospital admission with tenderness in the umbilical and right iliac quadrants, voluntary guarding but no organomegaly or abdominal distension, and preserved bowel sounds. Management: Baseline investigations (complete blood count, C-reactive protein, erythrocyte sedimentation rate, blood culture sensitivity, and stool and urine microscopy) and serum amylase and lipase were normal. Ultrasound showed mesenteric lymphadenopathy but no pancreatitis or appendicitis. Computed tomography (CT) demonstrated circumferential wall thickening in distal ileum with clustering of distal ileal loops, posterior and lateral to the cecum, extending into right paracolic gutter, suggestive of pericecal hernia. Child received conservative management and improved. Definitive surgical reduction was deferred due to negative parental consent. Conclusion: To conclude, internal abdominal hernia is rare in children with nonspecific clinical presentation. CT should be considered when underlying etiology of acute abdomen is not found on the basis of history, examination, and baseline investigative workup. Early intervention helps in reducing the morbidity and mortality to great extent.